Low and high reynolds number study of fluid-structure interaction problems - Rafael Nascimento Ihi (2014)
The present work is concerned with studying fluid-structure interaction problems using a high-fidelity representation for the fluid. In particular, the research aims to analyze the aeroelastic behavior of rigid airfoils and cylinders with elastic constraints, with emphasis in the effects of the inclusion of viscous terms in the aerodynamic formulation. The aerodynamic operator is constructed from the results of flow simulations using a computational fluid dynamics (CFD) tool which solves the 2-D Reynolds-averaged Navier-Stokes (RANS) equations with appropriate turbulence closures. Both low and high Reynolds number flow conditions are addressed in the present investigation. An in-house developed CFD solver is used for the simulations. Studies of low Reynolds number flows are directed towards addressing the physical phenomena present in the wake of cylinders, as well as their effects on the bodies present in the flow. The typical applications of interest in such cases are vortex-induced vibration problems which can arise in many practical scenarios, ranging from satellite launch vehicles at the launch platform to underwater risers in the petroleum industry. The study of such low Reynolds number flows has also been used as a building block in the process of developing the computational tools for addressing the fluid-structure interaction problems of interest here, since the computational requirements in such cases are much less stringent. Studies performed at high Reynolds number flows are directed towards typical aeroelastic stability analyses of lifting surfaces at transonic conditions. The aeroelastic system of interest is represented by a rigid NACA 0012 airfoil-based typical section with both plunge and pitch elastic degrees of freedom. Root locus stability analyses of the aeroelastic system are performed in order to predict the flutter onset point for a given flight condition. Results obtained in the present work indicate that the simulation capability implemented is adequate for handling the fluid-structure interaction problems of interest. However, as expected, computational requirements become very severe for the high Reynolds number flows and several numerical techniques have to be brought to bear in order to allow treatment of such aeroelastic problems in a sufficiently efficient manner.